Talent management implications - Ruyle, Kim E. (Henry Stewart Talks, 2014)
Importance of employee engagement, Impacts on organizational restructuring, Research-based drivers of engagement, Suggestions for leveraging engagement drivers during restructuring, Differentiation of talent, High potential talent, High professional talent, Emerging talent, Learning agility, Implications of organizational design schemas for talent management